Audience perceptions of news media on the Covid-19 pandemic: relations among media credibility, subjective well-being and fear of missing out - Vieira, Lívia; Aquino, Sibele (Brazilian journalism research, 2022)
ABSTRACT – This article pairs journalism studies and social psychology to investigate, with a quantitative method, audience perceptions of news media in the initial stages of the Covid-19 pandemic in Brazil by verifying the relations among media credibility, subjective well-being (SWB), and fear of missing out (FoMO). All told, 306 Brazilians took part in this study, answering a questionnaire to elicit demographic data, perceptions of media credibility, and behavioral characteristics. The findings revealed high averages of measures of news media credibility, with over 70% of respondents evaluating the work of the press as excellent or good. People with higher averages of negative affects tended to perceive the news media as more reliable. Furthermore, individuals who reported fear of missing out on the news during Covid-19 experienced more negative affect, and attributed greater credibility to news media. These findings show that in a time of fear and uncertainty, citizens seem to trust solid institutions more, accepting their reports less critically. We also found that unknown risks can attract attention more than regular events, tending to keep vigilance on specific news. Future studies can add additional measures of FoMO and use more diverse samples in different contexts. RESUMO – Este artigo aproxima os estudos de jornalismo e a psicologia social para investigar, com um método quantitativo, as percepções da audiência sobre a mídia noticiosa nos estágios iniciais da pandemia Covid-19 no Brasil, verificando as relações entre credibilidade da mídia, bem-estar subjetivo (BES) e fear of missing out (FoMO). Participaram deste estudo 306 brasileiros, que responderam um questionário demográfico, uma escala de credibilidade da mídia e questões sobre características comportamentais. Os resultados revelam que as médias das medidas de credibilidade da mídia são altas, com mais de 70% dos entrevistados avaliando o trabalho da imprensa como excelente ou bom. Pessoas com médias mais altas de afetos negativos tendem a perceber a mídia como mais confiável. Além disso, os indivíduos que relatam medo de perder notícias durante a Covid-19 experienciam mais afetos negativos e também dão mais credibilidade para a mídia. Argumenta-se que, em uma época de medo e incerteza, os cidadãos parecem confiar mais em instituições sólidas, aceitando seus relatos de forma menos crítica. Também é discutido que eventos com riscos desconhecidos podem atrair mais atenção do que acontecimentos regulares e isso mantém a vigilância sobre notícias específicas. Estudos futuros podem adicionar medidas adicionais de FoMO e usar amostras mais diversas em diferentes contextos. RESUMEN – Este artículo aborda los estudios de periodismo y psicología social para investigar, con un método cuantitativo, las percepciones de la audiencia sobre los medios de comunicación en las primeras etapas de la pandemia de Covid-19 en Brasil, verificando las relaciones entre la credibilidad de los medios, el bienestar subjetivo (BES) y el fear of missing out (FoMO). En este estudio participaron 306 brasileños, quienes respondieron un cuestionario demográfico, una escala de credibilidad mediática y preguntas sobre características de comportamiento. Los resultados revelan que los promedios de las medidas de credibilidad de los medios son altos, con más del 70% de los encuestados calificando el trabajo de prensa como excelente o bueno. Las personas con promedios más altos de afecto negativo tienden a percibir los medios como más confiables. Además, las personas que reportan miedo a perderse noticias durante el Covid-19 experimentan más efectos negativos y también dan más credibilidad a los medios. Se argumenta que, en una época de miedo e incertidumbre, los ciudadanos parecen confiar en instituciones más sólidas, aceptando sus cuentas de manera menos crítica. También se discute que los eventos con riesgos desconocidos pueden atraer más atención que los eventos regulares y esto mantiene al tanto de noticias específicas. Los estudios futuros pueden agregar medidas adicionales de FoMO y utilizar muestras más diversas en diferentes contextos.